India's and Pakistan's strategies in Afghanistan : implications for the United States and the region - Hanauer, Larry; Chalk, Peter; Center for Asia-Pacific Policy (Rand Corporation); Rand Corporation. National Security Research Division; Rand Corporation (Santa Monica, CA : RAND, 2012)
India and Pakistan have very different visions for Afghanistan, and they seek to advance highly disparate interests through their respective engagements in the country. Pakistan views Afghanistan primarily as an environment in which to pursue its rivalry with India. India pursues domestic priorities (such as reining in anti-Indian terrorism, accessing Central Asian energy resources, and increasing trade) that require Afghanistan to experience stability and economic growth. Thus, whereas Pakistan seeks to fashion an Afghan state that would detract from regional security, India would enhance Afghanistan$1 (Bs stability, security, economic growth, and regional integration. Afghanistan would welcome greater involvement from India, though it will need to accommodate the interests of multiple other external powers as well. India has a range of options for engaging Afghanistan, from continuing current activities to increasing economic and commercial ties, deploying forces to protect Indian facilities, continuing or expanding training for Afghan forces, or deploying combat troops for counterterrorism and counterinsurgency missions. To avoid antagonizing Pakistan, India is likely to increase economic and commercial engagement while maintaining, or perhaps augmenting, military training, though it will continue to conduct such training inside India. Increased Indian engagement in Afghanistan, particularly enhanced Indian assistance to Afghan security forces, will advance long-term U.S. objectives in central and south Asia. As the United States prepares to withdraw its combat forces from Afghanistan in 2014, it should therefore encourage India to fill the potential vacuum by adopting an increasingly assertive political, economic, and security strategy that includes increased security assistance.s
Introduction -- India -- Pakistan -- Afghanistan -- Implications for the United States -- Implications for India -- Conclusion.
"International Programs at RAND."
"RAND Center for Asia-Pacific Policy."
Includes bibliographical references (p. 59-72).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Afghanistan -- Foreign relations -- India; Afghanistan -- Foreign relations -- Pakistan; India -- Foreign relations -- Afghanistan; Pakistan -- Foreign relations -- Afghanistan; United States -- Foreign relations -- Afghanistan; United States -- Foreign relations -- South Asia